Strategi Cyber Public Relations dalam Membangun Citra Lembaga : Studi Deskriptif di Perseroan Terbatas Pendidikan Maritim dan Logistik Indonesia - Carolina Fernanda Diaz Aprianto; Nani Nurani Muksin (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
The development of digital technology has transformed how institutions communicate with the public, including the Maritime and Logistics Education Corporation of Indonesia (PT PMLI). This study is motivated by the strategic role of Cyber Public Relations in building institutional image in the digital era. The research focuses on how PT PMLI implements Cyber PR strategies to establish its institutional image. The objective is to identify the strategies applied and how the image is built in digital spaces. This study employs Ronald D. Smith’s Cyber PR Strategy Theory and Veljkovic’s Institutional Image Theory, using a qualitative descriptive method through in-depth interviews with five internal and external informants. The findings show that PT PMLI conducts situation analysis and audits using a SWOT approach, with strengths in digital integration and proactive approaches, and weaknesses in limited human resources and state-owned enterprise regulations. Opportunities come from digital innovation and external collaboration, while threats include the spread of hoaxes and sensitive data exposure. The strategic objectives focus on increasing audience engagement through interactive and educational content, as well as maintaining online reputation through consistent and responsive communication. PT PMLI utilizes its website and social media platforms Instagram, TikTok, and YouTube and develops trend-based content evaluated through media plans and engagement indicators.